Green leaf to inorganic leaf: a case study of ZnO - Sathu, Naveen K.; Devaraji, Perumal; Gopinath, Chinnakonda S. (Journal of Nanoscienceand Nanotechnology, 2016)
Can we use green leaves, available freely in our gardens, as a template for making inorganic leaf, while retaining the nanospace available within the leaf architecture. The answer is 'yes', and it is demonstrated with inorganic leaf made up of ZnO, by intercalating Zn2+ ions into the porous channels of the champa (Plumeria, Magnolia champaca) tree leaves. TEM studies reveal a variety of macro-micro-nanospace available in the inorganic leaf ZnO (IL-ZnO), and suggest the possibility of exploiting the same to produce natural nano-architecture for various applications. A speciality of the present work is the maximum suppression of defects in photoluminescence of IL-ZnO leaf, compared to the commercial ZnO, which is exploited for light harvesting through chemical conversion. Benzene to phenol conversion was studied in UV light and IL-ZnO show significant conversion and yield demonstrating C-H activation at ambient temperature.